The Temporal dimension in the study of knowledge bases: Approaches to understanding knowledge creation and representation over time - Adler, Melissa; Tennis, Joseph T.; Milojević, Stas̆a; van Hooland, Seth; Rogers, Corinne; West, Jevin D. (American Society for Information Science and Technology. Meeting. Proceedings of the ... ASIST Annual Meeting, 2013)
The panel explores the theoretical, methodological, and design aspects of the temporal dimension in the study of knowledge creation and representation and offers insights in both the challenges and the promising future directions. The goal of the panel is to start a collaborative discussion around a number of important themes. Categories and Subject Descriptors Applied computing • Document management and text processing • Information systems • Content analysis and feature selection • Information systems • Clustering and classification General Terms Your general terms must be any of the following 16 designated terms: Management, Measurement, Documentation, Design, Languages.